BAHASA ARAB AL-QUR'AN KE DALAM BAHASA INDONESIA: KAJIAN HERMENEUTIKA DAN SERAPAN BENTUK DIGLOSIA, INTERFERENSI, INTEGRASI HINGGA LINGUA FRANCA DALAM PENDIDIKAN ISLAM - Tamam, Mohammad Badru (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2018)
Arabic plays a major role in the work of the repertoire of Indonesian vocabulary, both in the fields of religion, literature, philosophy, law, politics, and education. Islamic education is oriented towards efforts to embody the Divine values ??in each student's personality; Islamic education is a human effort to internalize the attributes of Allah that are in him; The power and absoluteness of God in all its dimensions must be seen in all components of Islamic education, both in purpose, material, and other educational components. This paper aims to describe the Study of Islamic Education Hermeneutics and Absorption of Diglosia, Interference, Integration to the lingua franca of the Arabic Al-Qur'an into Indonesian. From the discussion concluded: 1) Although in many places the Al-Qur'an states the clarity of its verses, in the Al-Qur'an hermeneutical level invites scholars and writers to explain and understand the content with the birth of tons of books and references on their interpretations; 2) the fact that the Qur'anic language supplies the lingua franca, but various linguistic groups treat the same. There is no